CLINICAL CASE OF LATE DIAGNOSIS OF SWYER'S SYNDROME IN A 19-YEAR-OLD PATIENT - Еlgina, Svetlana Ivanovna; Rudaeva, Elena Vladimirovna; Moses, Vadim Gelievich; Moses, Kira Borisovna; Chernykh, Natalya Stepanovna (Mother and Baby in Kuzbass, 2026)
The article presents a rare clinical case of Swyer syndrome (pure gonadal dysgenesis 46,XY) in a 19-year-old patient who presented with complaints of primary amenorrhea and the absence of secondary sexual characteristics. The relevance of the case is due to the late diagnosis of the disease, which is usually detected during adolescence. The article describes the difficulties of differential diagnosis, key laboratory and instrumental data (karyotype 46,XY, hyperandrogenemia, and rudimentary gonads), and provides an individualized plan for multi-component therapy, including hormone replacement therapy (HRT), psychological support, and surgical prevention of gonadoblastoma.The article concludes that Swyer syndrome should be included in the differential diagnosis of all cases of primary amenorrhea, regardless of the phenotype.
Keywords: Swyer syndrome; pure gonadal dysgenesis 46,XY; primary amenorrhea; hypergonadotropic hypogonadism; gonadectomy; hormone replacement therapy; differential diagnosis